Do the Parts Add Up? Textual Systems and Segments of Sijie Ji (The Four Seasons) in Ming Anthologies. - Tan Tian Yuan (Journal of Chinese Ritual, Theatre & Folklore / Mínsú Qǔyì, 2024)
Sijie ji ... (The Four Seasons) is a set of four plays believed to have been composed in the mid-Ming. Each of these four plays is based on an episode related to a season in the lives of four famous literati: Du Fu (spring), Xie An (summer), Su Shi (autumn), and Tao Gu (winter). The full texts of these plays are no longer extant, but because they were widely popular during the Ming dynasty, excerpts of various shapes and forms can be found in more than twenty qu anthologies dating from as early as 1553. In other words, Sijie ji is a lost work, of which only certain parts are preserved, and exclusively so, through anthologies. How, for a work whose partial survival is closely connected to anthologies, do we approach this body of disparate, anthologized drama parts that all appear to be associated with Sijie ji? This paper explores the significance of reading these segments of Sijie ji not necessarily as parts of an elusive whole but instead as individual, meaningful textual units belonging to more than one textual system; it also considers the role of anthologies in textual relations and the circulation of knowledge within qu texts and across various genres.